Respiratory Activity and Pro-Oxidant/Antioxidant Balance of Rat Liver after Hypothermic Storage in Presence of Bencyclane Fumarate - Sosimchyk, I. A.; Cherkashina, D. V.; Somov, A. Yu.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2010)
The influence of bencyclane fumarate on mitochondria respiratory parameters, peroxidation process intensity and antioxidant enzyme activity of rat liver after hypothermic storage and normothermic reperfusion was investigated. The uncoupling effect of bencyclane on oxidative phosphorylation processes was shown both after storage and reperfusion. Partial prevention of TBARS basal level increase and antioxidant enzyme activity decrease in liver after cold storage in the presence of1 mMof bencyclane were observed.